Health & Wellness Texas - Meeks, Linda (McGraw-Hill, 2006)
For 3rd GradersMacmillan/McGraw-Hill Health&Wellness provides students with accurate, standards-based health content. The program focuses on ten Health Life Skills , including teaching students to make responsible decisions and to set health goals at each grade level. Macmillan/McGraw-Hill Health&Wellness is designed so that teachers can easily cover the core health materials and provide students with the content, skills, and the knowledge they need to lead healthy lives.